Pengembangan Bahan Ajar Perubahan Iklim Berbasis Literasi Sains Bermuatan Karakter Rasa Ingin Tahu Peserta Didik SMP - Khairunisa Khairunisa; Chairil Faif Pasani; Sauqina Sauqina (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to describe the validity of climate change teaching materials based on science literacy and curiosity character of junior high school students. The research method used is research and development (R&D) through the modified four-D (4 D) model. This modul development procedure includes three stages, whisch are define, design and develop. The subjects of this research and development include 5 expert validators. The type of data obtained is quantitative data in the formdof product validation questionnaire scores. The results of research and development of junior high school science teaching materials based on science literacy and characterised by curiosity on the topic of climate change by expert validators obtained validity results with a total of 0.90 with valid criteria. This is reviewed from three aspects: (1) content feasibility scored 0.90 with valid criteria, (2) presentation feasibility aspect scored 0.88 with valid criteria, (3) linguistic feasibility aspect scored 0.92 with valid criteria. So it can be concluded from all the validity tests that the teaching materials developed are classified as valid criteria.